(untitled) (Brazilian Journal of Radiation Sciences, 2023)
When handling unsealed radioactive sources, radiological protection attention must be taken to avoid unnecessary exposure and radioactive contaminations, and an important and necessary practice to prevent such contaminations is the use of gloves when handling these sources. The present work aimed to determine the effectiveness of contamination protection provided by different types of disposable polymeric gloves used in Nuclear Medicine Service in Clinic Hospital of Porto Alegre, testing the main radiopharmaceuticals used at this site: [99mTc]sodium pertechnetate, [18F]FDG and [131I]sodium iodide. The analysis was performed using the wipe test inside gloves intentionally contaminated on the outside with these radiopharmaceuticals. The radiation detector used to measure the contamination was a NaI(Tl) scintillator well-type counter. The results indicate that three types of gloves analyzed protect the user from [99mTc]sodium pertechnetate and [18F]FDG contamination, for permanence times with the glove after contamination for up to 15 min (interval tested). For [131I]sodium iodide, gloves are completely effective in protection as long as they are used for a time interval after contamination of the external surface of up to: Latex – 5 min; Vinyl – 5 min; Nitrile – 10 min. Among them, the nitrile glove are the most effective, since contamination was not observed on the inner face for times equal to or less than 10 min; and, for an interval of 15 min, the percentage of permeation obtained was lower than the other two types: 3.3 times lower than vinyl glove permeation and 1.3 times lower of the latex glove permeation. It was also possible to estimate the skin dose rate due to contamination caused by iodine permeation for each glove case and time tested.